Influence of temperature of quenchant on some mechanical properties of medium carbon steel - Adedayo, Victor (Journal of Production Engineering, 2018)
The study investigated influence of temperature of quenching water on some mechanical properties of medium carbon steel was investigated. The mechanical properties investigated are hardness, toughness and tensile strength. The medium carbon steel samples were machined to required dimensions and heated to austenization temperature of 9300C and quenched in water maintained at temperatures of 00C, 350C, and 1000C. Control samples were also machined, but not heat-treated. The mechanical properties of the quenched and control samples were determined through standard property evaluation procedures. The results show that the mechanical properties are dependent on the temperature of the quenchant water used. The microstructures also show a dependence on the temperature of the quenchant.